Maternal antenatal stress has little impact on child sleep: results from a prebirth cohort in Mexico City - Chatterjee, Avik; Thompson, Jennifer W.; Svensson, Katherine; Tamayo y Ortiz, Marcela; Wright, Robert; Wright, Rosalind; Tellez-Rojo, Martha; Baccarelli, Andrea; Cantoral, Alejandra; Schnaas, Lourdes; Oken, Emily (Sleep health, 2018)
Maternal antenatal stress may influence offspring development and behavior, but any association with child sleep is unknown. From 2007 to 2011, we recruited pregnant women in Mexico City to the Programming Research in Obesity, Growth, Environment, and Social Stressors prebirth cohort. Mothers completed the Perceived Stress Scale (PSS, a 4-item questionnaire assessing past-month stress) and the Crisis in Family Systems measure assessing negative life events (NLEs; how many domains among the 11 assessed in which the mother experienced a stressful event in the prior 6 months)—with higher scores reflecting higher stress—and provided 5 timed salivary samples per day on 2 consecutive days, from which we derived cortisol area under the curve, slope, and awakening response. At age 4-6 years, children's sleep was estimated using accelerometry over a 7-day period. We performed secondary analysis of associations of antenatal maternal stress with child sleep duration and efficiency (time asleep/time in bed) using linear regression adjusted for maternal and child characteristics. Among 594 mother-child dyads, mean antenatal PSS score was 5.2 (SD = 3.2) out of 16, and mean NLE was 3.2 (SD = 2) out of 11; child sleep duration was 7.7 hours (SD = 0.7), and sleep efficiency was 79% (SD = 6). There was no association between any of the stress measures—PSS, NLE, or salivary cortisol—and sleep duration or sleep efficiency in adjusted or unadjusted models. Among mother-child dyads in a Mexico City cohort, antenatal stress was not associated with important changes in child sleep at 4-6 years.